Rozważania o narracji budowanej wokół argumentu: „w świetle archeologii”. - Sołtysiak, Michał (Folia Praehistorica Posnaniensia, 2020)
“In the light of archaeology…” means a statement or conclusion based on archaeological sources, its practice and theoretical models used in it. But the range of possibilities and persuasiveness of all such statements is very wide. A typical lack of contemporary historiographic literature is the writer’s failure to define his own research attitude. Researchers also rarely want to confront their own subjectivity and define their views before they start presenting their explanations for the topic under study. This applies to both the research attitude, evaluation and purposefulness of the sources used, the scope of using the achievements and workshop of anthropology, and the issue of the narrative nature of archaeological writing itself. The aim of this article is to discuss the need for a more substantive attention to theoretical assumptions in archaeological writing, especially in the aspect of creating a historiographic narrative in historical archaeology. While attention is put on belonging to a given theoretical trend, the issues of narrative, persuasive procedures and noticing the narrative style that is chosen are less frequently analyzed. These are very significant characteristics of a given text, as they are directly directed to the reader, i.e., the person to whom our research and conclusions are presented. This text is, in accordance with the above considerations, also a commentary on the existing state and an attempt to draw attention to the need for the most conscious approach to one’s own scientific workshop.